Influence of Ag, Au and Pd noble metals doping on structural, optical and antimicrobial properties of zinc oxide and titanium dioxide nanomaterials. Issue 3 (March 2019) - Pathak, Trilok K.; Kroon, R.E.; Craciun, Valentin; Popa, Marcela; Chifiriuc, M.C.; Swart, H.C.
Abstract: Oxide materials (ZnO, TiO2 ) doped with noble metals were synthesized using the combustion technique. The results of the addition of Ag, Au, and Pd up to a concentration of 2 mol% on the structural, optical, morphological and antimicrobial properties was considered. X-ray diffraction experiments revealed that the crystal structure of the host materials remained unaltered despite doping with noble metals. From the scanning electron microscopy results, it was evident that the doped nanoparticles aggregated in clusters of different sizes in the host matrix. The plasmonic effect was also observed in the absorbance spectra of the different doped materials. The obtained materials have shown promising antimicrobial features. All ZnO materials exhibited a high antimicrobial activity, with very low minimum inhibitory concentration values, against the planktonic growth of all tested Gram-positive and Gram-negative bacterial strains. All doped materials exhibited very good anti-biofilm activity, the lowest minimal biofilm eradication concentration values being registered for ZnO doped with Au and Pd toward Escherichia coli and for ZnO doped with Ag against Candida albicans . These results indicate the potential that these materials have for antimicrobial applications in the fields of biomedicine and environmental protection.